β-Cell Deficit in Obese Type 2 Diabetes, a Minor Role of β-Cell Dedifferentiation and Degranulation - Butler, Alexandra E. (J Clin Endocrinol Metab, 2016)
CONTEXT: Type 2 diabetes is characterized by a β-cell deficit and a progressive defect in β-cell function. It has been proposed that the deficit in β-cells may be due to β-cell degranulation and transdifferentiation to other endocrine cell types. OBJECTIVE: The objective of the study was to establish the potential impact of β-cell dedifferentiation and transdifferentiation on β-cell deficit in type 2 diabetes and to consider the alternative that cells with an incomplete identity may be newly forming rather than dedifferentiated. DESIGN, SETTING, AND PARTICIPANTS: Pancreata obtained at autopsy were evaluated from 14 nondiabetic and 13 type 2 diabetic individuals, from four fetal cases, and from 10 neonatal cases. RESULTS: Whereas there was a slight increase in islet endocrine cells expressing no hormone in type 2 diabetes (0.11 ± 0.03 cells/islet vs 0.03 ± 0.01 cells/islet, P < .01), the impact on the β-cell deficit would be minimal. Furthermore, we established that the deficit in β-cells per islet cannot be accounted for by an increase in other endocrine cell types. The distribution of hormone negative endocrine cells in type 2 diabetes (most abundant in cells scattered in the exocrine pancreas) mirrors that in developing (embryo and neonatal) pancreas, implying that these may represent newly forming cells. CONCLUSIONS: Therefore, although we concur that in type 2 diabetes there are endocrine cells with altered cell identity, this process does not account for the deficit in β-cells in type 2 diabetes but may reflect, in part, attempted β-cell regeneration.